PARIWISATA ALTERNATIF MENDUKUNG PROGRAM PEMBANGUNAN BERKELANJUTAN DAN EKONOMI KERAKYATAN - Made Ruki (Politeknik Negeri Bali, 2013)
This paper analyzes the role of tourism in supporting sustainable development, and economic empowerment. So far tourism has greatly contributed to the economic growth and employment, but it also worries because the negative impact caused is very complex, both in terms of social, cultural, economic, and natural resources and the environment. It is a paradox in the lives of mankind today especially associated with the current development paradigm, namely sustainable development that was declared by the United Nations through the Rio Summit, 1992, which aimed to conserve natural resources and the environment. To answer that, then it is pushed to streamline the model of tourism known as alternative tourism. How can the alternative tourism support sustainable development programs? That is what will be further discussed through this paper, and how it can empower a community economic development. This post data is collected from various sources of literature and other reliable sources on the internet, then analyzed and compiled into a complete text.